2017
DOI: 10.1097/md.0000000000008957
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of short-term outcome of laparoscopic surgery versus conventional open surgery on colorectal carcinoma

Abstract: Objective:The aim of this article is to study the superiority and safety of laparoscopic surgery for colorectal carcinoma.Summary Background Data:Laparoscopy in rectal cancer is still not recommended as the treatment of choice by National Comprehensive Cancer Network guidelines. Laparoscopic rectal surgery is more complex and technically demanding, especially for mid and low rectal cancer.Methods:A computer-based online research of retrospective or prospective studies addressing laparoscopic surgery versus con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 59 publications
1
19
1
Order By: Relevance
“…In previous publications about elective surgeries, laparoscopy has demonstrated decreased complications such as SSIs and hospital LOS. 39 In contrast, our study demonstrated no difference in terms of complications including SSI. Similarly, Trejo-Avila et al 40 performed a singlecenter retrospective study and found no statistically significant difference in complications when comparing 19 patients who underwent laparoscopic surgery to 38 who underwent open surgery for both blunt and penetrating abdominal trauma.…”
Section: Discussioncontrasting
confidence: 77%
“…In previous publications about elective surgeries, laparoscopy has demonstrated decreased complications such as SSIs and hospital LOS. 39 In contrast, our study demonstrated no difference in terms of complications including SSI. Similarly, Trejo-Avila et al 40 performed a singlecenter retrospective study and found no statistically significant difference in complications when comparing 19 patients who underwent laparoscopic surgery to 38 who underwent open surgery for both blunt and penetrating abdominal trauma.…”
Section: Discussioncontrasting
confidence: 77%
“…Laparoscopy has been used increasingly over the past years, but data regarding the oncologic resection quality compared to open surgery are still scarce. This study aimed to the Very positive short-term effects and immediate advantages of the laparoscopic approach are described in various publications, such as reduced blood loss [19][20][21][22][23][24][25][26], shorter hospitalization time [20][21][22][23][24][25][26][27][28][29][30][31][32], faster bowel movement recovery [20,22,24,25,33], fewer complications [14, 19-21, 28, 34], a better view in the low pelvic area [21,26,35,36], and a lower short-term mortality rate [28,34,37]; however, negative elements such as increased operation time [19,[22][23][24][25][30][31][32] and higher costs [25] have also been reported. The prolonged operation time for laparoscopy seems to be due to the degree of experience, as there was no significant difference in a Chinese study where all patients were treated by the ...…”
Section: Discussionmentioning
confidence: 99%
“…Our study have the similar conclusion with other searches. [34,35] Besides, laparoscopic surgery group significantly decreased the incidence of postoperative complication compared with the open surgery group.…”
Section: Discussionmentioning
confidence: 99%
“…There were some similar meta-analyses of open surgery versus laparoscopic surgery for patients with colorectal cancer. Tong et al [34] summarized 9 clinical trials and supported that laparoscopic surgery appears to be a better alternative therapy for patients with colorectal cancer as compared to the open surgery. Zhang et al [35] summarized fifteen publications which were published between 2007 and 2017, and reported that hand-assisted laparoscopic surgery (HALS) was associated with shorter hospital days, postoperative hospital duration and so on.…”
Section: Discussionmentioning
confidence: 99%